Net primary production in the Labrador Sea between 2014 and 2022 derived from ocean colour remote sensing based on ecological regimes - E. Devred; S. Clay; M. Ringuette; T. Perry; M. Amirian; A. Irwin; Z. Finkel (Remote Sensing of Environment, 2025)

Shelf‐basin gradients shape ecological phytoplankton niches and community composition in the coastal Arctic Ocean (Beaufort Sea) - M. Ardyna; M. Babin; E. Devred; A. Forest; M. Gosselin; P. Raimbault; J.‐É. Tremblay (Limnology and Oceanography, 2017)
The contiguous Arctic shelf is the green belt of the Arctic Ocean. Phytoplankton dynamics in this environment are driven by extreme physical gradients and by rapid climate change, which influence light and nutrient availability as well as the growth and ecological characteristics of phytoplankton. A large dataset collected across the Canadian Beaufort Shelf during summer 2009 was analyzed to assess how the interplay of physical and biogeochemical conditions dictates phytoplankton niches and trophic regimes. Nonmetric multidimensional scaling and cluster analysis demonstrated marked partitioning of phytoplankton diversity. Elevated phytoplankton biomass (∼ 2.41 μg Chl a L −1 ) was observed in association with the surface mixed layer near the coast, close to the mouth of the Mackenzie River, and at the shelf‐break as a result of nutrient‐rich Pacific water intrusions. The coastal communities were supported by high levels of nitrogen nutrients and were taxonomically uniform, with diatoms accounting for 95% of total cell numbers. By contrast, adjacent oceanic waters were characterized by low autotrophic biomass near the surface (∼ 0.09 μg Chl a L −1 ) and below the mixed layer (∼ 0.23 μg Chl a L −1 ) due to mainly nutrient limitation. However, the oceanic community was more diverse with a mixed assemblage of diatoms and small mixotrophs/heterotrophs near the surface and a predominance of autotrophic nanoflagellates at depth. We conclude that as climate change intensifies freshening and stratification in the Western Arctic Ocean, coastal hotspots of high autotrophic productivity may play an even greater role in supporting Arctic marine ecosystems while offshore environments become increasingly oligotrophic.

Obtaining Phytoplankton Diversity from Ocean Color: A Scientific Roadmap for Future Development - Astrid Bracher; Heather A. Bouman; Robert J. W. Brewin; Annick Bricaud; Vanda Brotas; Aurea M. Ciotti; Lesley Clementson; Emmanuel Devred; Annalisa Di Cicco; Stephanie Dutkiewicz; Nick J. Hardman-Mountford; Anna E. Hickman; et al. (Frontiers in Marine Science, 2017)